Absent Arm Swing and Dual Tasking Decreases Trunk Postural Control and Dynamic Balance in People With Parkinson's Disease - Siragy, Tarique; Nantel, Julie (Frontiers in Neurology, 2020)
Introduction: Falling during walking is a common occurrence in people with Parkinson’s Disease and is closely associated with severe social and medical consequences. Recent evidence demonstrates that arm swing affects dynamic balance in healthy young adults, however, it remains unexamined what its effect is in people with Parkinson’s Disease, particularly when combined with a secondary dual-task. Methods: Twenty people with Parkinson’s Disease (63.78±8.97) walked with two arm swing conditions (absent and normal) with and without a secondary dual-task. Data were collected on a split-belt treadmill CAREN Extended-System (Motek Medical, Amsterdam, NL). Average and standard deviations for trunk linear and angular velocity were calculated along with their instantaneous values (during foot-strikes) in all three axes. Averages and Coefficient of Variations for step length, time and width, Margin of Stability and Harmonic Ratios were also calculated. Results: Compared to normal arm swing, absent arm swing reduced the least affected leg’s average step length and increased its step length Coefficient of Variation while increasing step time Coefficient of Variation in the most affected leg. Further, absent arm swing reduced trunk sagittal instantaneous angular velocity (least affected leg) and reduced sagittal instantaneous linear velocity (bilaterally). For the vertical axis, absent arm increased the trunk’s average angular velocity but reduced its instantaneous linear velocity and angular velocity standard deviation (least affected leg). Additionally, the Margin of Stability increased when the arms were absent (least affected leg). Alternatively, dual-tasking reduced average step time (most affected leg) and increased the step width Coefficient of Variation (bilaterally). Additionally, dual-tasking increased the frontal plane’s average angular velocity, instantaneous linear velocity standard deviation (bilaterally), and instantaneous angular velocity standard deviation (least affected leg). For the vertical axis, dual-tasking increased average linear and angular velocity standard deviation as well as instantaneous angular velocity standard deviation (bilaterally). Conclusion: Findings suggest that participants attempted to control extraneous trunk movement (due to absent arm swing) through compensatory responses in both lower and upper extremities. However, participants appeared to predominately compensate on their least affected side. Contrastingly, modifying mediolateral foot placement appeared to be the main means of maintaining walking stability while dual-tasking.